IMPLEMENTASI AKAD MURABAHAH DALAM PEMBIAYAAN KEPEMILIKAN RUMAH (KPR) PADA PT BANK BRISyariah KCP JOMBANG - Hidaya Rafiqa, Tria; Sudarwanto, Tri; Hidayati, Athi’ (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2019)
This research is a descriptive qualitative research which aims to know the application of murabahah principle applied by BRISyariah KCP Jombang on mortgage financing (KPR) as well as mechanism of mortgage financing proposal (KPR). Data obtained in this research through observasi, interview and documentation study. BRISyariah KCP Jombang provides home financing products with alternative buy new house and buy second home. The implementation of murabahah principle in mortgage financing (KPR) is done based on the principles of sharia, the fulfillment of conditions in the transaction and the pillars murabahah. The mechanism for submission of mortgage financing (KPR) is done by checking the financing report from Bank Indonesia (BI). If the reporting result is good, then the proposed financing will be realized. But if the reporting of financing is not good, then the proposed financing can not be realized.Key Word: Murabahah in mortgage financing (KPR).